Cotton ( Gossypium species) research-a pursuit towards self-sufficiency and export - KAIRON, M S; RAO, M R; VENUGOPALAN, M; SINGH, MAHENDRA (The Indian Journal of Agricultural Sciences, 2013)
The textile sector contributes to one-third of export earnings of India and cotton (Gossypium spp) alone constitutesnearly 70% of raw material. In the 3 distinct agro-ecological regions of cotton cultivation (Northern zone. Southern zoneand Central zone) productivity is highest in the Northern zone and lowest in Central zone. During the first two 5-Year-PlanPeriods released varieties'made significant impact in Punjab. Haryana, Maharashtra, Gujarat and Tamil Nadu. Theachievements made during the post-All-India Co-ordinated Cotton Improvement Project era. coupled with basic andstrategic research resulted in spectacular quantitative and qualitative changes in the cotton scenario. The productionincreased from 5.266 million bales during 1966-67 to 17.8 million bales during 1996-97. with a wide range in fibrequality parameters (6s to 120s) to fulfil the requirements of textile industry. The article deals with genetic improvement,production technology, plant protection and transfer of technology in cotton. Future thrust areas arc also suggested forfurther improvement in cotton production and productivity.